O programa de educação continuada dos gestores da educação pública paulista no contexto das reformas educacionais dos anos 1990 - Cruz, Sônia Maria de Sousa Santa (2008)
This study aims to identify and understand the differences in terms of context, organization, purpose, target audience, themes, actions and assessment between the two moments where was the Continuing Education Program managers of the network state of education in Sao Paulo for the government Covas. The first time is what occurred in the period de1996 to 1998, even in the first term of his government. That programme was characterised by being a program that aimed to meet the demands identified with the direct participation of the subjects involved, within each of the 19 Poles distributed in the territory Paulista, under the responsibility of different agencies. The research for that moment was to focus the work of the PUC-SP in Pole 4, which occurred in the city of Sao Paulo and the themes of Subproject Leaders. The second moment is the completion of the Circuit Management, which occurred in the period from 2000 to 2002, so now in the second term of government Covas. Programme which had as its features centralized planning, the development of more theoretical issues of character and far way from the reality of school units. While the first time was characterized as the stage of deployment of the first steps to reform the public school state of Sao Paulo promoted by that government, the second time it could be called a consolidation of the policies implemented in the inicial period. Identify and apprehend the differences between those two moments, through the study of the characteristics of each of the programs of continuing education allow the connections of each moment of the programme of training of managers with the broader context of educational policies and reforms that are sued within the state. This relationship was having a background to which revealed the mediations between the school and social system of production at the time of international crisis of capitalism and the advance of neoliberalism. The research used qualitative nature of the analysis as a tool documentary primary colleting data.